A result on fractional k-deleted graphs
Let k≥ 2 be an integer, and let G be a graph of order n with n≥4k-5. A graph G is a fractional k-deleted graph if there exists a fractional k-factor after deleting any edge of G. The binding number of G is defined as 26741 bind (G)={|N_G(X)||X|:eq XV(G),N_G(X) eq V(G)}. 26741 In this paper, it is proved that if bind (G)>(2k-1)(n-1)k(n-2), then G is a fractional k-deleted graph. Furthermore, it is shown that the result in this paper is best possible in some sense., number=1, journal=MATHEMATICA SCANDINAVICA, author=Zhou, Sizhong, year=2010, month=Mar., pages=99–106